(3fRgI GdCdHGH GdLGeYI dafhf GdBOGHs - (3YHO Gddg Hf YHO Gddg Hf SdGeg GdCOcGhj GdTGaYj GdeYQha HGdeDPfs ((3YeQ Hf GdNWGH s)
(3ChdgG (B:s
(3MeOkG def Rjf eMGad GdNdaGA HeMGSf GdCOHGA, hCfgV gege dGcJSGH GdeYGdj, aGcJSHhG ef MddgG OjHGLkG ePgHkG s
(3BNQgG (B:s
(3haj GdUMa YGbH, haj GdRHhQ aGQhb, hYfO Gddg JYGdi Wg, hYfO GdeDefjf eMeO, hocfjJg CHhGdbGSe s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B137 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQjI (B(6858) s
Keywords: (3GdCOHs